2019
DOI: 10.1038/s12276-019-0260-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PP2A activity by H2O2 during mitosis disrupts nuclear envelope reassembly and alters nuclear shape

Abstract: Many types of cancer cells exhibit abnormal nuclear shapes induced by various molecular changes. However, whether reactive oxygen species (ROS) induce nuclear deformation has not been fully addressed. Here, we show that hydrogen peroxide (H 2 O 2 ) treatment induced concentration-dependent alterations in nuclear shape that were abolished by pretreatment with the antioxidant N-acetyl-L-cysteine or by catalase overexpression. Interestingly, treatment with H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
(94 reference statements)
1
4
0
Order By: Relevance
“…H 2 O 2 impairs protein phosphatase 2A (PP2A) activity, which is responsible for removing Akt phosphorylations on T308 and S473 (19)(20)(21)(22). In agreement with these earlier studies, we also observed that H 2 O 2 treatment promoted Akt phosphorylation (Fig.…”
Section: Energy Deprivation Promotes Tsc22d4-akt1 Interactionsupporting
confidence: 92%
“…H 2 O 2 impairs protein phosphatase 2A (PP2A) activity, which is responsible for removing Akt phosphorylations on T308 and S473 (19)(20)(21)(22). In agreement with these earlier studies, we also observed that H 2 O 2 treatment promoted Akt phosphorylation (Fig.…”
Section: Energy Deprivation Promotes Tsc22d4-akt1 Interactionsupporting
confidence: 92%
“…We suppose that nuclear shape alterations in CHO cells are probably a direct result of osmotically induced stress. A recent finding reveals that exposure to elevated ROS concentrations induces nuclear shape alterations including fragmentation and folding due to aberrations in the reassembly of the nuclear envelope in cancer cells (Ahn et al, 2019). The authors discovered that the cells are most vulnerable during mitosis, so it is unclear if the structures we observed on Days 6 and 8 in the "feed" condition are artifacts of uncompleted mitotic division disrupted by osmolality increase on Day 3/4 or if these have evolved during the fed-batch gradually with time.…”
Section: Single-cell Observation Via Confocal Microscopy and Iccmentioning
confidence: 99%
“…Excessive ROS may damage important cellular components and lead to defects in DNA repair mechanism and antioxidant defense system, thus changing cell homeostasis [ 2 ]. ROS have influences on cell proliferation, the imbalance of cell growth and tumorigenesis, which also play important roles in growth factors, mitosis, and development of cancers [ 3 , 4 , 5 ]. However, nucleic acids are often transformed into various modified bases when exposed to oxygen free radicals.…”
Section: Introductionmentioning
confidence: 99%